2018
DOI: 10.1155/2018/7975013
|View full text |Cite
|
Sign up to set email alerts
|

Botulinum Neurotoxin Application to the Severed Femoral Nerve Modulates Spinal Synaptic Responses to Axotomy and Enhances Motor Recovery in Rats

Abstract: Botulinum neurotoxin A (BoNT) and brain-derived neurotrophic factor (BDNF) are known for their ability to influence synaptic inputs to neurons. Here, we tested if these drugs can modulate the deafferentation of motoneurons following nerve section/suture and, as a consequence, modify the outcome of peripheral nerve regeneration. We applied drug solutions to the proximal stump of the freshly cut femoral nerve of adult rats to achieve drug uptake and transport to the neuronal perikarya. The most marked effect of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 71 publications
1
7
0
Order By: Relevance
“…Similar to Cobianchi et al [82], Irintchev et al [87] observed that BoNT/A application to the axotomized femoral nerve modulates spinal responses and enhances motor recovery in rats. The authors applied BoNT/A only once using the time frame between axonal membrane damage and sealing, considering that this temporal window would be sufficient to "prime" the initial responses of motoneurons to injury, in particular their deafferentation, and, thus, eventually achieve long-term effects on regeneration without the need of repeated drug delivery to the injury site.…”
Section: Botulinum Toxin and Nerve Regeneration After Peripheral Injusupporting
confidence: 52%
“…Similar to Cobianchi et al [82], Irintchev et al [87] observed that BoNT/A application to the axotomized femoral nerve modulates spinal responses and enhances motor recovery in rats. The authors applied BoNT/A only once using the time frame between axonal membrane damage and sealing, considering that this temporal window would be sufficient to "prime" the initial responses of motoneurons to injury, in particular their deafferentation, and, thus, eventually achieve long-term effects on regeneration without the need of repeated drug delivery to the injury site.…”
Section: Botulinum Toxin and Nerve Regeneration After Peripheral Injusupporting
confidence: 52%
“…The femoral nerve is an alternative and suitable model for peripheral nerve injury. Crucial findings regarding nerve regeneration and neurophysiology were revealed with the help of this model (Brushart, ; Brushart, Gerber, Kessens, Chen, & Royall, ; Brushart et al, ; Irintchev et al, ; Kruspe et al, ; Madison, Archibald, & Brushart, ; Madison, Sofroniew, & Robinson, ; Meng et al, ; Robinson & Madison, ; Tuffaha et al, ). Its advantageous features, compared with the sciatic nerve model, include more feasible functional evaluation and absence of limb contractures or automutilation (Irintchev, ; Irintchev et al, ).…”
Section: Discussionmentioning
confidence: 96%
“…In terms of key benefits, the femoral nerve model seems to offer another advantage, which is the missing of feared complications such as autotomy, contractures of the limb or skin ulcerations, but it has yet to be proven that these do never occur or just far less frequent than in the sciatic nerve model (Irintchev, ). In the last years, studies of peripheral nerve repair and regeneration in the rat femoral nerve model increased considerably (Adel et al, ; Hong, Hong, Gu, Lin, & Yin, ; Irintchev, Guntinas‐Lichius, & Irintchev, ; Meng et al, ; Xia et al, ). In contrast to the sciatic nerve model, no satisfactory method had been published to perform functional analysis in the femoral nerve model until 2005 (Irintchev, Simova, Eberhardt, Morellini, & Schachner, ).…”
Section: Introductionmentioning
confidence: 99%
“…Although substantial advances in surgical procedures have and continue to be made [ 4 ], recovery of normal function after nerve injury is often elusive, especially when the injury is close to the spinal cord, and regeneration of the injured nerve over long distances is required to achieve reinnervation of the target [ 30 , 74 ]. Physical therapy is integral to optimal recovery, yet the pain associated with injury or surgery may limit the ability of patients to perform the required exercises.…”
Section: Attributes Of Bont/a That Make a Promising Therapeutic Agent...mentioning
confidence: 99%
“…To exploit the critical time window for successful recovery, development of therapeutic agents to accelerate the rate and accuracy of reinnervation would be desirable [ 3 ]. During the last decade, numerous candidates have been examined, almost all in animal studies, including corticosteroids [ 25 ], the immunosuppressant drug FK-506 [ 26 ], insulin-like growth factor-1 (IGF-1) [ 27 ], vascular endothelial growth factor (VEGF) [ 28 ], transforming growth factor-β1 (TGF-β1) [ 29 ], brain-derived neurotrophic factor (BDNF) [ 30 ], 4-aminopyridine (4-AP) [ 31 ], and botulinum neurotoxin A (BoNT/A) [ 30 , 32 ]. A comprehensive discussion of drug candidates can be found in a recent review by Bota and Fodor [ 33 ].…”
Section: Introductionmentioning
confidence: 99%